STUDI TENTANG PRODUK USAHA KERAJINAN BORDIR DI KECAMATAN KURANJI KOTA PADANG - MARLINA, IKA; Zahri, Wildati; Idrus, Yenni (Journal of Home Economics and Tourism, 2015)
Problems were found in the development of embroidery in District Kuranji designmotifs used are still using pre-existing motifs, due to lack of knowledge of artisans increating the design motif, this makes the product less variable results. The purpose of thisstudy is to describe the design motif embroidery, embroidery techniques and types ofproducts kerajinanbordir. The research method uses descriptive qualitative method. Thetype of data in the form of primary and secondary data. The technique of collecting datathrough observation, interviews and documentation. The data analysis is done with tekbiksnow ball sampling by using an interactive model analysis techniques, namely the model ofdata reduction, data presentation, and making conclusions. The results of that study,embroidery motifs contained in the embroidery business in District Naturalists Kuranji isthe motive of plant and animal motifs like motif of leaves, stems, grass, jasmine, roses,orchids, lotus, butterfly. Geometric motifs such as rectangular motifs, from the later in thestylized motifs into a decorative ornament. Decorative embroidery pattern consists of;Sowing pattern, pattern fringes, pattern fills the field and the free pattern. The combinationof colors using a combination of neutral colors, Monocromatis and Complement.Embroidery techniques used there are 5 techniques: embroidery techniques suji liquid, fullsuji, fantasy embroidery, embroidery overlay / kerancang (includes: kerancang seats, chisel,cross, wheels, broom, chaotic, board, wrap, cut, rail, fish eye) and the application ofembroidery techniques. Type of product produced is mukena, materials for clothingapplique, embroidery material for skirts, embroidered materials for the robe and materialsfor kebaya embroidery. Expected results of this embroidery craft products can continue tobe preserved and enhanced ability to compete and market share.Kata kunci: Produk kerajinan bordir di Kecamatan Kuranji.